2011
DOI: 10.1111/j.1475-1305.2011.00807.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Thermal Cycles on the Deformation State at the Crack Tip of Crystallisable Natural Rubber

Abstract: This article deals with the effect of temperature variations on crack tip kinematics in rubbers, especially in crystallising rubbers. In such materials, the high deformation level encountered at the crack tip engenders the formation of crystallites. As a consequence, the crack tip is reinforced and resists crack growth. However, this phenomenon is significantly affected by variations in material temperature. This is classically observed at the macroscopic scale in terms of crack propagation rate and path. In t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…To the knowledge of the author, only that reported in Ref. [60] investigate the effect of temperature on the kinematic field at the crack tip to link it to the evolution of the microstructure. The authors use full-field measurements to characterise the effect of changes in the microstructure on the kinematic field at the crack tip.…”
Section: Dic At the Macroscopic Scalementioning
confidence: 99%
See 2 more Smart Citations
“…To the knowledge of the author, only that reported in Ref. [60] investigate the effect of temperature on the kinematic field at the crack tip to link it to the evolution of the microstructure. The authors use full-field measurements to characterise the effect of changes in the microstructure on the kinematic field at the crack tip.…”
Section: Dic At the Macroscopic Scalementioning
confidence: 99%
“…Digital image correlation at smaller scales is difficult, because of the large displacement of the points at the crystallization l l l l Figure 1: Kinematic field measurement at the crack tip of stretched carbon-filled natural rubber [60]. From the top left corner to the top right corner, the rubber specimen was previously cut with a razorblade before being stretched to put a heated metallic cylinder inside the crack.…”
Section: Dic At the Microscopic Scalementioning
confidence: 99%
See 1 more Smart Citation
“…For hyperelastic materials, studies of the thermal and deformation behaviour of rubbers near the tip of a crackvia DIC and thermal imagingwere carried out by Le Cam et al [14] and Martinez et al [15,16]. Rublon et al [17] used DIC to investigate the near tip behaviour in a filled natural rubber under fatigue loading, but DIC results were not used to evaluate a fracture mechanics-related quantity.…”
Section: Introductionmentioning
confidence: 99%
“…However, it will be shown that the proposed elastic approach works well as long as the stress-strain response is adequately described by a phenomenological law such as Ogden's model, which neglects the actual crystallisation physics: the approach, in fact, allows determining the value of the J-integral correctly without having to consider what happens in the fracture process zone. In this work, the focus is on the determination of the J-integral for materials assumed to be hyperelastic; for details on the aspects related to the physics of fracture and to the process zone phenomena in these materials, the reader is referred to [14,15,23,29].…”
Section: Introductionmentioning
confidence: 99%